If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 4x + -1(2x + -14) Reorder the terms: 90 = 4x + -1(-14 + 2x) 90 = 4x + (-14 * -1 + 2x * -1) 90 = 4x + (14 + -2x) Reorder the terms: 90 = 14 + 4x + -2x Combine like terms: 4x + -2x = 2x 90 = 14 + 2x Solving 90 = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 90 + -2x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 90 + -2x = 14 + 0 90 + -2x = 14 Add '-90' to each side of the equation. 90 + -90 + -2x = 14 + -90 Combine like terms: 90 + -90 = 0 0 + -2x = 14 + -90 -2x = 14 + -90 Combine like terms: 14 + -90 = -76 -2x = -76 Divide each side by '-2'. x = 38 Simplifying x = 38
| 3x-(x+26)=180 | | 5y-10=40 | | 4w-8w=28 | | 2x+(x-33)=90 | | -4=7x+1-8 | | 4(x-5)=x+4 | | 11n=10+16 | | 4x+(x+35)=90 | | (3x/(x-7))-((x+7)/x)=0 | | (3x/(x-7))-((x+7)/x) | | x-3=(5x-1)^1/2 | | 7g=6 | | 700-2x=50+2x | | -49.95-20x= | | x^2+4x-y=7 | | V=x(14-2x)(10-2x) | | 5(2x-7)=3(4x+9) | | 2x/5=x+6 | | 7m-3=3m+17 | | 4+10x=(x+9)4 | | x-5=20/5 | | 5x-1=-51 | | 9x+13=2x+174 | | t^3-5t^2+4t=0 | | -8+2x=-16 | | 12-7x=69-28x | | -4.9x^2+22t+42=0 | | 47+0.5x= | | -3-x=-1 | | 3+2x=-11 | | -5x-7=48 | | 1-4x=-11 |